Design Fuzzy Disturbance Observer with Neuro-Fuzzy Invers Model for Parallel Hybrid Electric Vehicle Speed Controller - Yoga Alif Kurnia Utama; Trihastuti Agustinah; Josaphat Pramudijanto (IPTEK Journal of Proceedings Series, 2015)
In this paper, fuzzy disturbance observer with neuro-fuzzy invers model is proposed to control speed of parallel hybrid electric vehicle (PHEV) with change in disturbance. Disturbance make unstable speed so that actual speed of PHEV is not equal to reference speed. Fuzzy disturbance observer is used to make actual speed of PHEV is equal to reference speed when disturbance applied on it. The result show that fuzzy disturbance observer can reject the disturbance so that so its speed has more stable .